2020
DOI: 10.3390/min11010011
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan with Bentonite and Biochar in Ni-Affected Soil Reduces Grain Ni Concentrations, Improves Soil Enzymes and Grain Quality in Lentil

Abstract: Ecological and human health risks associated with Ni-affected soils are one of the major attention seeking issues nowadays. The current investigation is based on the usage of biochar (BR), chitosan (CN), bentonite (BE), and their mixture to immobilize Ni in a Ni-polluted soil and accordingly contracted Ni distribution in lentil plant parts, improved grain nutritional quality, antioxidant defense system, and soil enzymatic activities. The soil was initially amended with CN, BE, and BR and later lentil was grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 72 publications
4
6
0
Order By: Relevance
“…In our study, the average AB-DTPA concentrations in the steel factory were higher than the reported values by Crispo et al [44], who studied 20 UK cities. Tanzeem-ul-Haq et al [45] studied Ni-affected soils, and reported that Ni availability in a soil of pH 7.03 was 3.02% of the total, comparable to the availability reported in our work.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the average AB-DTPA concentrations in the steel factory were higher than the reported values by Crispo et al [44], who studied 20 UK cities. Tanzeem-ul-Haq et al [45] studied Ni-affected soils, and reported that Ni availability in a soil of pH 7.03 was 3.02% of the total, comparable to the availability reported in our work.…”
Section: Discussionsupporting
confidence: 90%
“…Notable increases in CAT, SOD, and POD activities and increased ROS scavenging were reported following BC addition in drought-stressed maize varieties [ 47 ]. A profound increase in SOD and CAT activity by BC and CHT application was reported in Ni-stressed lentil plants, confirming enhanced ROS scavenging to protect the plants against oxidative damage [ 52 ]. Similarly, the application of BC increased SOD and CAT activities in Ni-stressed mung bean plants [ 60 ].…”
Section: Discussionmentioning
confidence: 74%
“…Similar results were also observed with CHT application in water-stressed barley, where Pro accumulation was reduced by regulating the water pressure and RWC [ 20 ]. Tanzeem-ul-Haq et al [ 52 ] reported that combined CHT and BC supplementation enhanced the RWC of lentil plants in nickel (Ni)-spiked soils and improved plant growth by improving moisture retention and plant—water relationships.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations